Performance of the third generation striped catfish, Pangasianodon hypophthalmus Sauvage, 1878 as results of the selection for bodyweight character in Freshwater Aquaculture Fisheries Center, Sungai Gelam, Jambi - Irwan Irwan; Dinar Tri Soelistyowati; Odang Carman; Ronny Rachman Noor (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Selective breeding of striped catfish (Pangasianodon hypophthalmus Sauvage, 1878) has been conducted at BPBAT Sungai Gelam to produce a growth line with mass selection method. Until 2018, the selective breeding program has produced three generations. Therefore, it was necessary to evaluate the performance of the third generation growth line (G3Ps) at the reproductive, seed and grow-out phase compared to the second generation the base population (G2Ds). A total of 10 pairs of broodstock (G3Ps and G2Ds) were spawned then the seeds were raised for 120 days in the media with regular water exchange (first treatment: T1) and without water exchange (second treatment: T2). The results showed that the number of eggs per gram of G3Ps (1600±124 eggs g-1) was significantly different from G2Ds (1490±101 eggs g-1). The bodyweight of G3Ps seeds at aged 40 days larger than G2Ds with selection response is 32.25%, while survival and feed efficiency were not significantly different. At the grow-out phase, between treat-ments were not significantly different and there was no interaction between lines and treatments for all the characters measured (p>0.05). The bodyweight of G3Ps was larger than the G2Ds with response selection 18.41% in T1 and 42.6% in T2. The control used was the base population so that the selection response obtained was an accumulation of three generations. Thus the selection response per generation was 6.14% in T1 and 14.20% in T2 measured at 162 days from hatching. It can be concluded that there is an improvement in the character of bodyweight for the third generation of growth line (G3Ps) as results of the selection at BPBAT Sungai Gelam both in good (T1) and bad environment (T2). Abstrak Seleksi ikan patin siam (Pangasianodon hypophthalmus Sauvage, 1878) telah dilakukan di BPBAT Sungai Gelam untuk meningkatkan pertumbuhan dengan metode seleksi individu. Sampai tahun 2018, seleksi tersebut telah meng-hasilkan tiga generasi. Penelitian ini bertujuan untuk mengevaluasi performa generasi ketiga galur pertumbuhan (G3Ps) pada tahap reproduksi, pertumbuhan benih, dan ukuran konsumsi dibandingkan dengan populasi dasar gene-rasi kedua (G2Ds). Sebanyak 10 pasang induk G3Ps dan G2Ds dipijahkan kemudian benih yang dihasilkan dibesarkan selama 120 hari pada media dengan pergantian air secara berkala (perlakuan pertama: T1) dan tanpa pergantian air (perlakuan kedua: T2). Hasil penelitian menunjukkan bahwa jumlah telur per gram adalah 1600±124 butir pada G3Ps, berbeda nyata dengan G2Ds yaitu 1490±101 butir. Benih G3Ps umur 40 hari memiliki bobot tubuh lebih besar diban-dingkan G2Ds dengan respons seleksi sebesar 32,25%, sedangkan sintasan dan efisiensi pakan tidak berbeda nyata. Pada tahap pembesaran ukuran konsumsi, antar perlakuan tidak berbeda nyata dan tidak ada interaksi antargalur dan perlakuan untuk karakter bobot tubuh, panjang baku, sintasan dan efisiensi pakan (p>0,05). Karakter bobot tubuh G3Ps lebih besar dibandingkan dengan G2Ds dengan respons seleksi total untuk tiga generasi sebesar 18,41% pada T1 dan 42,6% pada T2. Dengan demikian respons seleksi per generasi sebesar 6,14% pada T1 dan 14,20% pada T2 yang diukur pada umur 162 hari dari menetas. Disimpulkan bahwa terjadi perbaikan pada karakter bobot tubuh untuk galur pertumbuhan generasi ketiga (G3Ps) hasil program seleksi di BPBAT Sungai Gelam baik pada lingkungan baik (T1) maupun lingkungan buruk (T2).